Athermal physiological effects of microwaves on a cynobacterium Nostoc muscorum: evidence for EM-memory bits in water - Singh S.P.; Rai S.; Rai A.K.; Tiwari S.P.; Singh S.S.; Samarketu; Abraham J. (My University, 2025)
Athermal physiological effects of continuous wave and modulated microwaves were studied on a cynobacterium Nostoc muscorum. The study shows that different microwave frequencies in continuous wave and modulated modes produced significantly different physiological effects on the algae. Water-mediated bioeffects further present additional proof that water has the capability to remember the imposed electromagnetic field characteristics for an extended period of time. © 1994 IFMBE.